Ecofarming - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Kotchi Johannes, Ann Waters-Bayer, Reinhard Adelhelm, Ulrich Hoesle, 1989 'Ecofarming in agricultural development', 132pp. ISBN 3 8236 1163 1. Edited and published by GTZ (Deutches Gesellschaft fur Technische Zusammenarbeit)